Effect of modified atmosphere packaging on microbial flora changes in fishery products - Velu, Selvi; Abu Bakar, Fatimah; Mahyudin, Nor Ainy; Saari, Nazamid; Zaman, Muhammad Zukhrufuz (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Modified atmosphere packaging (MAP) has become a popular method for packaging foods as it can extend the shelf life of food with minimal quality defect. Oxygen, nitrogen and carbon dioxide are the common gases used in MAP, Oxygen and carbon dioxide inclusive as only these two gaseous have the preservative effects on the packed food product. Their effect on microbial changes of any food product throughout storage period is highly depend on type of the product and packaging materials, appropriate gas composition, storage temperature, the ratio between gas and product volume, and hygienic manner during processing and packaging. MAP with highest percentage of carbon dioxide is proven to be more effective than vacuum packaging in inhibiting the growth of spoilage and pathogenic bacteria in many fishery products. This article reviews the consequences of MAP towards microbial changes in fishery products.